Modernizing the Administration of Islamic Law in Nigeria through Digital Innovation: Opportunities and Challenges - Moses Adeolu AGOI; Bukola Abosede FOLARANMI; Achmad Tubagus Surur; Hendri Hermawan Adinugraha (Ahlika: Jurnal Hukum Keluarga dan Hukum Islam, 2026)
This research explores the modernization of Islamic legal administration in Nigeria through digital innovation, addressing the growing need to transition from inefficient manual judicial processes. The objective is to analyse the intersection of digital transformation and Shari’ah legal practice, identifying specific opportunities and obstacles within the Nigerian plural legal system. Applying a doctrinal and analytical methodology, the study reviews academic literature, statutory laws, and policy reports. The results identify significant opportunities, including increased judicial efficiency through e-filing and virtual hearings, and improved access to legal knowledge via AI-driven research tools and Shari’ah-sensitive chatbots. However, the study also highlights critical challenges, including poor broadband infrastructure, a digital literacy gap among practitioners, and the risk of compromising the theological authenticity of Shari’ah in a digital space. The main novelty lies in the argument that digital tools must be strictly contextualised within Islamic legal ethics, such as Maqasid al-Shari’ah, in which technology serves as a decision-support system rather than a replacement for human ijtihad. Ultimately, this research impacts the field by proposing a collaborative framework between scholars, technologists, and judicial institutions to create a sustainable digital Islamic legal ecosystem that balances technological innovation with doctrinal integrity.